The Negative Impact of Modern Western Science from The Perspective of Islamic Theology - Mugiarti, Resmi; Hutabarat, Rodesma; Amrillah, Rizki (JURNAL PENELITIAN KEISLAMAN, 2024)
This research examines the effects of modern Western science on faith and human responsibility as Earth's stewards (caliphs) from an Islamic theological perspective. It highlights the adverse impacts of modern science, including a weakening of faith, environmental degradation, resource exploitation, and diminishing human responsibility. Using a qualitative descriptive method with a literature-based approach, the study gathers data from books, journals, and scientific articles. The analysis identifies secularism, materialism, and anthropocentrism as underlying factors contributing to these issues. To mitigate the negative consequences, the study proposes several solutions: developing an Islamic science paradigm that integrates knowledge and religion, strengthening Islamic education to promote moral and spiritual values, and raising public awareness about the risks of unchecked modern science. By establishing a balanced, ethical approach to science and fostering a sense of responsibility as Earth's caliphs, we can ensure that scientific progress aligns with Islamic values and promotes the greater good.